2023
DOI: 10.1186/s40035-023-00369-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence of human pathogens implicated in Alzheimer’s disease pathology and the therapeutic efficacy of antimicrobials: an overview

Abstract: A wealth of pre-clinical reports and data derived from human subjects and brain autopsies suggest that microbial infections are relevant to Alzheimer’s disease (AD). This has inspired the hypothesis that microbial infections increase the risk or even trigger the onset of AD. Multiple models have been developed to explain the increase in pathogenic microbes in AD patients. Although this hypothesis is well accepted in the field, it is not yet clear whether microbial neuroinvasion is a cause of AD or a consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 158 publications
0
5
0
Order By: Relevance
“…In recent decades, the rise of the inflammation–pathogen infection hypothesis has ignited interest in the potential association between infections, specifically URIs, and the initiation and progression of AD [ 5 ], with several studies linking pathogens and related inflammatory pathways to AD pathology in human-derived samples and experimental models [ 25 , 26 , 27 ]. However, there has been no dedicated investigation into the relationship between the URI histories of individuals seeking medical care and their subsequent risk of developing AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the rise of the inflammation–pathogen infection hypothesis has ignited interest in the potential association between infections, specifically URIs, and the initiation and progression of AD [ 5 ], with several studies linking pathogens and related inflammatory pathways to AD pathology in human-derived samples and experimental models [ 25 , 26 , 27 ]. However, there has been no dedicated investigation into the relationship between the URI histories of individuals seeking medical care and their subsequent risk of developing AD.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly acknowledged that AD is a complex condition, shaped by a combination of genetic and environmental factors [ 3 ]. In recent years, the emergence of the inflammation–pathogen infection hypothesis has sparked interest in the potential link between infections, particularly upper respiratory infections (URIs), and the onset and advancement of AD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They include traumatic brain injury (TBI) and chronic traumatic encephalopathy (CTE) [ 178 , 179 , 180 , 181 ]. They also include viral [ 182 , 183 , 184 , 185 , 186 ] and bacterial [ 187 , 188 , 189 , 190 ] infections. Indeed, it has been shown that a number of herpes viruses, such as HHV1, HHV2, HHV3 (varicella zoster virus), HHV4 (Epstein-Barr virus), HHV5 (cytomegalovirus), HHV6A, HHV6B and HHV7, flaviviruses, such as Zika virus, Dengue fever virus, and Japanese encephalitis virus, human immunodeficiency virus, HIV, hepatitis viruses, such as HAV, HBV, HCV, HDV, HEV, SARS-CoV2 virus, Ljungan virus, influenza A virus, and Borna disease virus are associated with, increase the risk of, and can potentially cause AD.…”
Section: Unconventional Alzheimer’s Disease: Elicitation Of the Neuro...mentioning
confidence: 99%
“…A similar link was found between bacterial infections and AD. Thus, infection with spirochetal bacteria is associated with a ten-fold increased occurrence of AD, and a five-fold increase in in the occurrence of AD was caused by infection with Chlamidophyla pneumonia [ 187 , 188 , 189 , 190 ]. Neuroinflammation, systemic inflammation in general, and such inflammatory conditions as osteoarthritis and rheumatoid arthritis in particular, have been also strongly associated with Alzheimer’s disease [ 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 ].…”
Section: Unconventional Alzheimer’s Disease: Elicitation Of the Neuro...mentioning
confidence: 99%
“…While existing literature has robustly established the role of H 2 S as a circulatory biomarker for vascular disorders [61], burgeoning research is increasingly elucidating its complex roles within neurovascular compartments, particularly concerning Alzheimer's Disease (AD) [62]. Emerging investigations have transcended the focus on H 2 S solely as a modulator of amyloid-beta (Aβ) aggregation dynamics in neuronal cultures, delving into its function in regulating the transvascular clearance of Aβ peptides [63].…”
Section: The Dialectic Role Of Hydrogen Sulfide In Neurovascular and ...mentioning
confidence: 99%